Developing a competency assessment program for special librarians a basis for professional and career development - San Buenaventura, Gina B.; Cruz, Ma. Divina P. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2004)
The purpose of this study was to establish a competency assessment program for librarians using selected special librarians from various sectors as a benchmark. The objectives established were to: (1) develop a competency dictionary for librarians; (2) profile different library positions; (3) profile person incumbents; (4) identify competency gaps and overlaps; and, (5) develop specific interventions.
The groundwork of the study involved an extensive and intensive review of available literature both local and foreign; putting up of a workshop on competency development, interviews, and position and person profiling.
The population for this study consisted of Chief Librarians, Supervisors and Senior Librarians from the broadcast/media, business/corporate, government and international organizations. Respondents were asked to participate in the Competency Development Workshop.
The competency development workshop produced the following outcomes: review of the competency definitions, validation of the competency proficiency levels and overall approval of the competency dictionary. Forty-one (41) competencies were identified as required in the different library organizations. These were classified according to core competencies, 10; management competencies, 22; and technical competencies, 9.Fifty-three (53) library positions (14 chief librarians, 10 supervisors, 17 senior librarians and 12 entry-level positions) were profiled using the established competency dictionary. The profiling of library positions identified the required competencies and corresponding competency proficiency levels for different library positions/levels in the different sectors covered.
The results and findings of the interviews with the Chief Librarians and Library supervisors established the various competency gaps between LIS graduates and current entry-level library job incumbents.
The study provided recommendations on how the academic community, library practitioners and the different professional library associations can work together in the development of the necessary interventions to fill the identified competency gaps of librarians as figured out and determined by the competency profiling system.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Special librarians -- Philippines -- Manila Metropolitan Area